Students demand for higher education in tourism and the perception of gender issues in a tourism degree - Salgado, Manuel (2015)
Tourism Studies are considered as an autonomous scientific area in higher education (HE). Therefore, our analysis is based on its evolution in Portugal and the reality in relation to gender issues in this scientific field. This research intends to understand some trends in tourism education, especially in a national context, the characteristics of students’ demand in a tourism and hospitality higher education institution (HEI) and, specifically, the perception of gender issues by students taking the degree of Tourism and Leisure (TL). The Portuguese HEIs have invested significantly in this field and, in this context of growth, we analyse the School of Tourism and Hospitality (STH) to understand its vocational orientation and the specificities of the educational demand. The methodology relies on a literature review to contextualize the currentparadigms of HE in Tourism and its connection to gender issues. The analysis of primary and secondary information on key indicators is about the courses’ offer and students’ demand at the STH could help to understand the institutional framework. The primary data was obtained with an intentional sample of students from the TL degree. The marketing strategy of STH could be improved through better knowledge about the students’ profile and the adaptation of the educational offer.